Closure of small perforation in tympanic membrane by use of fat plug - Patel, Nehal R.; Patel, Vaibhav V.; Padavi, Dimpal; Prajapati, Mayur; Khokhani, Rachana M.; Sharma, Pooja A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic suppurative otitis media presents mostly with ear discharge and associated decreased hearing. Tympanoplasty is the established surgery for tympanic membrane perforation. Most commonly used graft material for tympanoplasty is temporalis fascia. Others are fascia lata, tragal perichondrium, tragal cartilage, fat. The objective of the study was to compare the graft taken up and hearing improvement following myringoplasty with use of fat. Methods: Patients of CSOM aged 10 to 65 years old with small central perforation which is dry for at least 3 weeks with normal middle ear mucosa and intact ossicular chain with mild conductive hearing loss. The present study was carried out in Ear, neck and throat (ENT) Department of SCL hospital, Ahmedabad from July 2016 till September 2018 and 25 patients were randomly selected fulfilling the above criteria. Result: The choice of graft affects not only the outcome of surgery, but also determines the complexity of the procedure and the time taken for the same. Study proves that fat is also a one of the good grafting material which is easily available and keep to prevent from major surgery. The results have been quite encouraging. Conclusion: Study proves that fat is also a one of the good grafting material which is easily available and keep to prevent from major surgery. An added advantage of this technique was the excellent post-operative quality of life of the operated patients, assessed in terms of the chronic ear survey and evident by the absence of the usual post-operative complaints following a conventional myringoplasty.